POSTHARVEST QUALITY OF 'DÉBORA' TOMATOES TREATED WITH ETHYLENE - ANDREUCCETTI, CAROLINE; FERREIRA, MARCOS D.; MORETTI, CELSO L.; HONÓRIO, SYLVIO L. (Revista Brasileira de Engenharia de Biossistemas, 2007)
Tomatoes are one of the most important vegetable crops grown in Brazil and the development ofpostharvesthandling processes is desirable. The main goal of this work was to evaluate thequality of 'Débora' tomatoes treated with ethylene. Treatments were accomplished using a gasmixture with ethyl (5%) diluted in compressed air, using a flow through system for 48 hours at thetemperature of 20±1ºC and relative humidity of 90±5%. After ethylene application, tomatoes werestored either at 20 ±1ºC or12.5±1ºC, and control fruits were kept in the same conditions. For eachmaturity color change, fruits were assayed for color, water loss, ratio soluble solids/titratable acidity,and ascorbic acid. Ethylene treated fruits showed higher color uniformity and ripened faster thanuntreated ones, as higher values of ratio (soluble solids/titratable acidity) with ripened. Highestwater loss percentages were shown for tomatoes stored at 20ºC. In general, the ethylene treatmentand the storage temperature did not influence the ascorbic acid contents. The utilization of ethyleneto ripe 'Débora' tomatoes is potentially feasible